Assessment of Police Trainees’ Satisfaction with the Public Safety Basic Recruit Course of The National Police Training Institute - Villa, Elizabeth B.; Jarque Jr., Vicente L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aimed to determine police trainees' satisfaction with the Public Safety Basic Recruit Course of the NPTI, and the significant difference in satisfaction between Criminology and non-criminology graduate police trainees. The study applied descriptive correlational research design and interviews using a self-made survey questionnaire for 218 respondents and prepared guided interview questions for five key informants from the graduating police trainees at NCRTC. The data obtained were collated, sorted, summarized, and subjected to statistical treatment methods. The result of the study revealed that police trainees were very satisfied with the Public Safety Basic Recruit Course. They greatly appreciated the quality of training program. However, facilities, equipment, and supplies needed attention and improvement. Interviews disclosed that despite high satisfaction, police trainees faced various challenges that dissatisfied them. These includes frequent shortages of water supplies, overcrowding of dormitories and classrooms, and insufficient faculty members. However, despite these, they remained optimistic that the training management can address it. Additionally, the study found that there was no significant difference in satisfaction between Criminology and non-criminology graduate police trainees. This suggests that both groups had similar levels of satisfaction, and highly appreciative with the training program. To enhance further the satisfaction of police trainees, the NPTI should focus on improving facilities, equipment, and supplies, and address the specific concerns raised by the trainees. Furthermore, an action plan should be developed, outlining realistic, measurable, and time-bound plans, programs, and activities to address the concerns of police trainees.